SUBGROUPS OF AMINO ACID SEQUENCES IN THE VARIABLE REGIONS OF IMMUNOGLOBULIN HEAVY CHAINS - Cunningham, Bruce A. (1969)
The amino acid sequence of the first 133 residues of the heavy (γ) chain from a human γG immunoglobulin (He) has been determined. This γ-chain is identical in Gm type to that of protein Eu, the complete sequence of which has been reported. Comparison of the two sequences substantiates the previous suggestion that there are subgroups of variable regions of heavy chains. The variable region of Eu has been assigned to subgroup I and that of He to subgroup II; on the other hand, the constant regions of the two proteins appear to be identical. Comparison of the sequence of the heavy chain of He with the heavy chain sequences determined in other laboratories suggests that the variable region of subgroup II is at least 118 residues long. The nature and distribution of amino acid variations in this heavy chain subgroup resemble those observed in light chain subgroups. These studies provide evidence that the translocation hypothesis applies to heavy as well as to light chains, viz., genes for variable regions (V) are somatically translocated to genes for constant regions (C) to form complete VC structural genes.